Growth inhibition and apoptosis induction by (+)-Cyanidan-3-ol in hepatocellular carcinoma. - Jitender Monga (Public Library of Science (PLoS), 2013)
The objective of this study was to evaluate the cytotoxicity of (+)-cyanidan-3-ol (CD-3) in human hepatocellular carcinoma cell line (HepG2) and chemopreventive potential against hepatocellular carcinoma (HCC) in Balb/c mice. The HepG2 cell line was treated with CD-3 at various concentrations and the proliferation of the HepG2 cells was measure by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl-tetrazolium bromide (MTT), sulforhodamine B (SRB) and lactate dehydrogenase (LDH) assays. Cell apoptosis was detected by Hoechst 33258 (HO), Acridine orange/ethylene dibromide (AO/EB) staining, DNA fragmentation analysis and the apoptosis rate was detected by flow cytometry. The HCC tumor model was established in mice by injecting N-nitrosodiethylamine/carbon tetrachloride (NDEA/CCl4) and the effect of CD-3 on tumor growth in-vivo was studied. The levels of liver injury markers, tumor markers, and oxidative stress were measured. The expression levels of apoptosis-related genes in in-vitro and in vivo models were determined by RT-PCR and ELISA. The CD-3 induced cell death was considered to be apoptotic by observing the typical apoptotic morphological changes under fluorescent microscopy and DNA fragmentation analysis. Annexin V/PI assay demonstrated that apoptosis increased with increase in the concentration of CD-3. The expression levels of apoptosis-related genes that belong to bcl-2 and caspase family were increased and AP-1 and NF-κB activities were significantly suppressed by CD-3. Immunohistochemistry data revealed less localization of p53, p65 and c-jun in CD-3 treated tumors as compared to localization in NDEA/CCl4 treated tumors. Taken together, our data demonstrated that CD-3 could significantly inhibit the proliferation of HepG2 cells in-vitro and suppress HCC tumor growth in-vivo by apoptosis induction.